Поэма Пушкина "Братья разбойники" = Pushkin's poem "The Robber Brothers" Комментарий = a commentary - Stepaništševa, Tatjana (University of Tartu Press, 2023)
The book is an extended commentary on Pushkin's poem "The Robber Brothers". The author redefines the poem's place in Pushkin's creative biography and provides a detailed line-by-line commentary. This poem by Alexander Pushkin has been considered peripheral among his "Southern Poems", and therefore researchers have paid little attention to it. The main cause of such lack of consideration was the specific history of the creation of "The Robber Brothers." Pushkin experimented with constructing a new poem at the intersection of different vectors of genre and style topical for both the poet and literature as a whole. Due to this dynamic tension, the concept of the poem became ambiguous - the choice of the plot composition and narrative methods were not determined. After making several attempts and sketches, Pushkin shortened his initial concept and created an author legend on the genesis of the poem, which was introduced to the first audience of readers as a disconnected fragment of a scattered whole, whereas the plot of the poem was depicted as based on a real event. Within Pushkin's corpus, "The Robber Brothers" remained primarily a literary monument of the author's rapid evolution during his "Southern" period. It proved to be an extremely concentrated experiment, ultimately without success.